High‐Temperature Synthesis of Amides from Alcohols or Aldehydes by Using Flow Chemistry. Issue 34 (28th October 2014) - Ambreen, Nida; Wirth, Thomas
Abstract: An efficient conversion of aliphatic and aromatic alcohols or aldehydes into the corresponding primary amides was successfully achieved by using flow chemistry. Excellent yields were obtained in very short reaction times, and thus this method offers an efficient alternative to traditional methods for amide formation. Abstract : An efficient and fast conversion of aliphatic and aromatic alcohols or aldehydes into the corresponding primary amides is successfully achieved at high temperatures by using flow chemistry.